Autocenzūros galia: Merkinės seniūno Antano Kazimiero Sapiegos 1722–1733 m. užrašai - Sarcevičienė, Jolita (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] The article focuses on the diary of daily activities of the elder of Merkinė Antoni Kazimierz Sapieha written during the period 1722–1733. It chronicles daily meetings, correspondence, estate administration issues, the author’s health condition, travel routes, cases heard by the Tribunal of the Grand Duchy of Lithuania and other various facts of daily activities. It excludes the thoughts of reflective type; there is a clear emotional distance between the author and the events being described. The author’s rhythm of life was not only determined by economic affairs but also the work sessions of public authorities – the Tribunal, dietines, the Diet. After analysing the topics of the information recorded in the diary, an assumption of self-censorship influencing the choice of the information to be recorded is raised. Therefore, the aim of the article is to present the topics of the information recorded in the source, to discuss their informational and parenetic type thus highlighting certain aspects which could testify that the author would select the information to be recorded as well as reveal the impact of self-censorship on the diary. Before undertaking to keep a diary, the author set himself a clear goal and consciously separated both a landlord’s life from that of a politician and the life of a public person from the life of a private person. With a focus on future readers, A. K. Sapieha censored his diary but concentrated on those events which had to or could shape his positive image in the eyes of his successors. Even though the source reveals diverse episodes from the daily life of the elder of Merkinė, it also provides a dim outline of the author’s personality.